1984
DOI: 10.1038/312458a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of murine interleukin-1 cDNA in Escherichia coli

Abstract: Interleukin-1 (IL-1), a peptide hormone produced by activated macrophages, possesses the ability to modulate the proliferation, maturation and functional activation of a broad spectrum of cell types and may play a major role in the initiation and amplification of immune and inflammatory responses through its action on these diverse cell populations. IL-1 exhibits microheterogeneity in terms of its relative molecular mass (Mr, 13,000-19,000) and charge properties, and although murine IL-1 has been purified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
260
0
8

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(273 citation statements)
references
References 26 publications
5
260
0
8
Order By: Relevance
“…Fig. 5(A) showed the alignment between the cloned PCR product ampli®ed by the IL-1a primers and the mouse IL-1a cDNA (Lomedico et al, 1984; Genebank accession number: X01450). The extremely high homology indicated that the fragment was ampli®ed from IL-1a cDNA.…”
Section: Con®rmation Of the Pcr Productsmentioning
confidence: 99%
“…Fig. 5(A) showed the alignment between the cloned PCR product ampli®ed by the IL-1a primers and the mouse IL-1a cDNA (Lomedico et al, 1984; Genebank accession number: X01450). The extremely high homology indicated that the fragment was ampli®ed from IL-1a cDNA.…”
Section: Con®rmation Of the Pcr Productsmentioning
confidence: 99%
“…26]; uPA; 1.2-kb PstI fragment of murine cDNA from pDB15 [29]; murine IL-1␤ [30]; ␤-actin, a 1.8-kb chicken ␤-actin cDNA fragment in pGEM2; c-fms, p755 containing the 3.7-kb mouse c-fms cDNA, obtained from L. Rohrschneider (Fred Hutchinson Cancer Research Centre, Seattle, WA); and lysozyme, pMLC, which contains a 780-bp fragment of mouse lysozyme M cDNA, obtained from R. Renkawitz (Max Planck Institute, Munich, Germany). Blots were reprobed with a synthetic 24-bp oligonucleotide (5Ј-CAT GGT AGG CAC GGC GAC TAC CAT-3Ј) complementary to murine 18S rRNA to control for gel loading.…”
Section: Plasmidsmentioning
confidence: 99%
“…The IL-1 cytokines consist of two polypeptides, IL-la and IL-1,B, that have essentially the same activity although they are the products of two different genes (4,30,31). The two polypeptides are produced as 31-kDa precursors which are subsequently processed to their 17-kDa active form (3,17).…”
mentioning
confidence: 99%
“…These cytokines can act individually or in concert to exert an influence on a target cell or tissue (reviewed in reference 2). The IL-1 cytokines consist of two polypeptides, IL-la and IL-1,B, that have essentially the same activity although they are the products of two different genes (4,30,31 …”
mentioning
confidence: 99%